Factors Affecting Corporate Social Responsibility Disclosure With Company Size As Moderating Variable (A Case Study of Indonesian Company) - Subing, Hesty Juni Tambuati; Daniyati, Milah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2025)
Corporate social responsibility (CSR) refers to a company's obligation to act ethically towards the environment and the communities in which it operates, which is manifested through the disclosure of information related to social and environmental activities. This research aims to examine the influence of profitability, measured by Return on Assets (ROA), liquidity, assessed through the Current Ratio (CR), and leverage, indicated by the Debt to Equity Ratio (DER), on CSR disclosure, with company size serving as a moderating variable. The study employs a quantitative research methodology, focusing on non-financial state-owned companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. A purposive sampling method was utilized to select a sample of seven companies for analysis. Data were collected through non-participant observation and subsequently analyzed using multiple linear regression analysis and moderated regression analysis (MRA), facilitated by SPSS version 26.0. The findings reveal that both profitability and liquidity have a significant positive effect on CSR disclosure, while leverage does not demonstrate a significant impact. Additionally, company size is found to moderate the relationship between profitability and CSR disclosure, as well as the relationship between leverage and CSR disclosure; however, it does not moderate the effect of liquidity on CSR. These results underscore the importance of financial performance indicators in influencing CSR practices and highlight the role of company size in shaping these relationships.